Real Estate Market Developments and Financal Sector Soundness - Hilbers, Paul (IMF Working Papers; Working Paper ;, 2001)
This paper analyses the characteristics and functioning of real estate markets. It focuses on the relationship between developments in these markets and the financial sector to determine under what circumstances real estate booms and busts can develop and how they can affect the health and stability of the financial system. It concludes that unbalanced real estate price developments often contribute to financial sector distress and that trends in real estate markets should be monitored closely in the context of financial sector assessments.